2014
DOI: 10.1016/j.alcohol.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The α2-adrenergic receptor agonist, clonidine, reduces alcohol drinking in alcohol-preferring (P) rats

Abstract: Evidence suggests that noradrenergic signaling may play a role in mediating alcohol-drinking behavior in both rodents and humans. We have investigated this possibility by administering clonidine to alcohol-drinking rats selectively bred for alcohol preference (P line). Clonidine is an α2-adrenergic receptor agonist which, at low doses, inhibits noradrenergic signaling by decreasing norepinephrine release from presynaptic noradrenergic neurons. Adult male P rats were given 24-h access to food and water and sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Hence, yohimbine, which also contains alpha-2 ARs antagonism may reinstates alcohol seeking after extinction (Marinelli et al, 2007). On the other hand, alpha-2 AR agonists may reduce alcohol consumption or alcohol-withdrawal symptoms (Opitz, 1990; Muzyk et al, 2011; Rasmussen et al, 2014; Fredriksson et al, 2015; Giovanitti et al, 2015). However, it has also been reported that specific agonists or antagonists of alpha-2 ARs may produce only minor changes in the voluntary alcohol drinking in alcohol-preferring rats (Korpi 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, yohimbine, which also contains alpha-2 ARs antagonism may reinstates alcohol seeking after extinction (Marinelli et al, 2007). On the other hand, alpha-2 AR agonists may reduce alcohol consumption or alcohol-withdrawal symptoms (Opitz, 1990; Muzyk et al, 2011; Rasmussen et al, 2014; Fredriksson et al, 2015; Giovanitti et al, 2015). However, it has also been reported that specific agonists or antagonists of alpha-2 ARs may produce only minor changes in the voluntary alcohol drinking in alcohol-preferring rats (Korpi 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, yohimbine, an alpha-2 AR antagonist can reinstate alcohol seeking after extinction (Funk et al, 2016; Marinelli et al, 2007). On the other hand, alpha-2 A AR agonists that may decrease availability of NE reduce alcohol consumption (Fredriksson et al, 2015; Opitz, 1990; Rasmussen et al, 2014). However, very few studies have investigated direct effects of alcohol on apha-2 ARs, particularly in relation to depressive-like characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that ethanol and saccharin consumption may have overlapping effects on (genetically-influenced) neurobiological systems involved in reward, such as the opioid, serotonin, and dopamine systems [110]. Consistent with this idea, P rats who were administered clonidine (a noradrenergic signaling inhibitor) reduced alcohol consumption and saccharin consumption, but not water consumption [111]. In another example, P rats who were administered TP-10 (a dual-specificity cyclic adenosine monophosphate/cyclic guanosine monophosphate-inhibiting enzyme inhibitor) reduced their alcohol and saccharin self administration [112].…”
Section: Aud Endophenotypes In Animal Modelsmentioning
confidence: 99%
“…Additonally, tolerance did not appear to develop following repeated daily treatments (Rasmussen, Kincaid, & Froehlich, 2015). Another study found that clonidine, an α2-adrenergic receptor agonist, can also reduce ethanol drinking by P rats (Rasmussen, Alexander, Malone, Federoff, & Froehlich, 2014; Rasmussen, Beckwith, Kincaid, & Froehlich, 2014). In addition, the triple monoamine uptake inhibitor (i.e., DAT, NET and SERT) DOV 102,677 reduced ethanol intake by P rats (Yang et al, 2012).…”
Section: Some Neurochemical Neuropharmacological As Well As Neurmentioning
confidence: 99%